Hygiene of Touristic Hotel Kitchens: The Case in Adiyaman, SE Turkey - Sabbag, Cigdem; Hepsag, Fatma (Pakistan Journal of Nutrition, 2011)
The need of hygiene education along with hygiene quality of kitchens at four Tourism Ministry licensed touristic hotels in Adiyaman, SE Turkey was determined. The evaluation is undertaken via interviews with 25 kitchen staff of the three and four star hotels. Majority of the kitchen staff (68%) did not receive training on hygiene before employment; others had trained on food and personnel hygiene by hotel managers who does not have profession on the subject matter. Due to lack of knowledge on hygiene of staff, the overall personnel hygiene is below country and international standards. Accordingly, staffs kitchen management was not considered as hygiene according to touristic measures of the Ministries of Tourism and Health although Adiyaman is one of the main touristic destinations of Turkey hosting more than 200.000 tourists annually. Unfortunately, only one hotel’s kitchen hygiene is classified as good. Thus, there is an urgent need for training along with continuous inspection of local authorities responsible for health and tourism.